Biocentric–networking landscape configuration of left-bank Ukraine - Удовиченко, Вікторія Віталіївна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The aim of the research is to determine the biocentric-networking landscape configuration (BNLK) contemporary structure as an important basis for the landscape planning tools implementation in the region, according to the results of analysis the factors of its formation and development, and structural-morphometric estimation. The method is based on the results of our mapping modelling of landscape-typological structure of the Left-Bank Dnipro of the Ukraine territory (at the level of landscape types) and the nature reserve fund. The region of the exploration is the Left-Bank of the Dnipro river which is understood as a totality of four administration regions of Ukraine, such as Poltava, Sumy, Kharkiv and Chernigiv. The BNLK contemporary structure was determined by using GIS-parcel MapInfo Professional 10.0.1, and landscape complexes data, including 1 552 objects of nature reserved fund (by 1.11.2016). The BNLK is understood as a totality of biocenters, biocorridors, interactive elements, buffer zones and “matrix”, which all together make a special system that supports the ecological equilibrium in a region. Thus, for the first time in the region all sorts of BNLK elements were differentiated according to the estimated level of forestation, nature reserve fund and landscape-typological structure. Also, we distinguished 88 biocenters and 51 biocoridors,that present different spatial-hierarchical levels, the mapping model of which also was done. All together, in the Left-Bank Dnipro river of Ukraine territory were determined 12 – national, 12 – regional, and 64 – local biocenters; also 4 – national, 5 – regional, and 41 – local (including 16 – at the ²-t level and 25 – at the ²²-nd level) biocoridors. The results received in a such way could be a good background for choosing distinguishing criteria of landscape planning typological units and for future use in landscape planning.